Kompetisi Portugal-Belanda dalam Perdagangan Senjata Api di Nusantara, 1498-1641 - Kurnia, Krisnaldi Putra; Zakaria, Mumuh Muhsin; Mahzuni, Dade (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
Firearms and gunpowder are commodities commonly sold during the early European arrival to Indonesia, including Nusantara. Similar to the spice trade, there was intense competition among the Europeans in arms trading. With that, the orientation of this research is to show the rivalry between 2 main trading factions on trading in Nusantara during the 16th and 17th centuries: Portugal and The Netherlands. As a historical study, this research applies the historical method as its research method. Reconstruction results show that European traders’ decision to make firearms an import commodity cannot be separated from the popularity of the war instrument in the warfare of their home continent. Initially, Portugal managed to consolidate its power as a dominant firearms trader in Nusantara after they conquered Malacca in 1511. Their domination slowly faded after the arrival of VOC ships during the late 16th century culminating in the takeover of Malacca in 1641. Therefore, it can be said that the firearms trading competition in Nusantara during this period reflects the trend of warfare at the time alongside the relations of various European nations outside their homelands.